ADMINISTRASI DAN SUPERVISI PENDIDIKAN ISLAM PEDOMAN PELAKSANAAN ADMINISTRASI - Meti Fatimah; Ahmad Suparno Basri Administration plays a crucial role in ensuring the smooth implementation of act; Abdullah Aufa Nadhif (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Administration plays a crucial role in ensuring the smooth implementation of activities across various sectors, including government, private, education, and community organizations. The development of implementation guidelines aims to establish orderly, effective, efficient, and accountable management of activities. Through these guidelines, each stage of activity—ranging from planning, implementation, to evaluation—can be systematically documented, thereby supporting transparency and improving organizational performance.